Teori Postmodrenisme dalam Studi Kasus Fenomena Pertumbuhan Ekonomi dan Industri Cina - Nurjannah (Journal of Diplomacy and International Studies, 2022)
In this adult era with the development of globalization which the world is rapidly advancing, thus the big number of thinkers of science due to the greater influence in people's lives. Therefore the life of globalization can not be separated from the name postmodernism, the birth of postmodernism because of the failure of the theory of modernism in handling the problem of modernization that aims to help the problems of society but instead it has a bad and irresponsible. Here the author will postmodernism theory in a case study of Chinese economic and industrial growth, industry is a pillar of China's economic support so that the more industries, the faster economic growth in China, but it will instead adversely affect the environment in China especially because of this modernization in globalization of the world thus post, modernism comes as new breakthrough ideas to solve the development problem of modernism. Therefore the researchers used a discrete analytic method with a qualitative approach in analyzing postmodernism in a case study of China's economic and industrial growth phenomena.